Important Elements for Inflation Targeting for Emerging Economies - Otker, Inci (IMF Working Papers; Working Paper ;, 2010)
This is the fifth chapter of a forthcoming monograph entitled "On Implementing Full-Fledged Inflation-Targeting Regimes: Saying What You Do and Doing What You Say." It examines whether certain conditions have to be met before emerging economies can adopt an inflation-targeting regime and provides some empirical evidence on the matter. The issues analyzed are the priority of inflation targeting over other goals, the absence of fiscal dominance, central bank independence, the degree of control over the policy interest rate, a sound methodology for forecasting, and the soundness of financial institutions and markets, and resilience to changes in exchange rates and interest rates.